Meningkatkan Minat Belajar Siswa Dalam Pembelajaran Seni Tari Dengan Metode Cooperative Learning Di Kelas VIII.4 SMP N 17 Padang - Fuby Candani; Indrayuda Indrayuda (SENDRATASIK UNP, 2019)
This research aimed to describe the students' learning interest in dance through the use of cooperative learning method in class VIII 4 of SMP Negeri 17 Padang. This type of research was Classroom Action Research. The research was conducted using 2 cycles, each cycle consisting of planning, implementation, observation, and reflection. The steps for analyzing data were data collection, data reduction, data verification and making conclusions. The results showed that the art of dance in class VIII 4 of SMP Negeri 17 Padang. Padang with the dance material previously decreased after the cooperative learning method of learning interest and the value of experienced students improved following KKM. The research result for student interest per cycle as the first cycle was 32.26% increasing and in the second cycle, there was an increase in interest by 25.8%. Overall, the result of the teacher's action using the cooperative learning method has been increased by 58.06%. It can be seen from 21 students who did not reach the KKM from dancing activities now only 3 students who have not reached the value of the KKM, but the value continues to increase from its initial value. It used to be a cooperative learning method for using arts learning teachers in class VIII 4 of SMP Negeri 17 Padang.